ANALYSIS OF THE BASIS OF PROFESSIONAL SKILLS OF STUDENTS IN THE PROCESS OF EXPERIMENTAL WORK - KosimovShavkatUrolovich; Mamatmuradova Nazira Choriyorovna (International Engineering Journal For Research & Development, 2020)
The article is based on scientific-theoretical ideas and practical-methodical recommendations developed and based on the research. and other tools to improve the methodological apparatus. Practical teachers cover the issues of innovative organizational and methodological structure of practical vocational education and the formation of students' professional knowledge, skills and competencies - the basis of professional skills, the organization of theoretical and practical training on practical vocational education.